PEMBENTUKAN KELEKATAN AMAN ORANGTUA PADA ANAK USIA DINI DALAM PEMBELAJARAN DARING - Octavian Dwi Tanto (JCE (Journal of Childhood Education), 2021)
The pandemic era has changed the face of the early childhood education learning model towards an online learning model. During this pandemic, online learning models are seen as more rational and safer to implement when the Covid 19 outbreak has not ended. However, the implementation of online learning has encountered many technical problems due to the adaptation factors of teachers, parents, and children who are not used to applying this learning model. In contrast to these technical problems, this study aims to reveal the positive side of implementing online learning in early childhood, especially for children aged 4 to 6 years. The online learning practice of early childhood education on YouTube is the object of observation which is discussed as well as being studied in depth. Data collection techniques in this study used documentation and observation data collection techniques that were limited to online learning content of early childhood education in Indonesia. The results of this study indicate that there is a secure attachment that is formed through the process of parenting and compassion for children during this activity. This study also found the supporting factors for the formation of secure attachment between parents and children, namely the emergence of online technical problems that precisely attached secure attachment between the two.